Ein Lied und sein Vor-Bild - Borengässer, Norbert M. (Zeitschrift für katholische Theologie, 2017)
A song was written in Innsbruck more than 375 years ago which is certainly not the oldest text dedicated to the Mother of God, but it has remained one of the most popular up to today. The motif »Schutz und Schirm« (shelter and protection) finds parallels in patristics: shelter and security which Mary offers as special intercessor before God. The motif of the protective cloak under which Mary guards Christen dom or the world in general is now added, and the author examines the question of which model may have served the songwriter as a visual aid in 1640.